LASER MACHINING HEAD HAVING AN OPTICAL ELEMENT - VEES, DOMINIK; WEICK, JÜRGEN-MICHAEL; RUPP, THOMAS (2024)
An optical element for installation in a laser processing machine has a surface that is optically unused and/or not subject to a laser beam during operation of the laser processing machine when the optical element is installed in the laser processing machine, and a transponder disposed in a region on or near the surface and containing readable information relating to the optical element.